1990
DOI: 10.1161/01.res.66.4.1040
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane B2 in cardiac lymph. Effect of superoxide dismutase and catalase during myocardial ischemia and reperfusion.

Abstract: Neutrophils have been implicated in the genesis of myocardial ischemia-reperfusion injury, and their mechanism of action has been linked to the production of reactive oxygen species, fatty acid-derived prostanoids, and leukotrienes. In this study, we examined the potential relation between production of reactive oxygen species and cyclooxygenase-derived autacoids by studying the effects of superoxide dismutase (SOD) and catalase (CAT) on the rise in thromboxane formation observed with myocardial ischemia and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…26 Furthermore, Ito et al 15 demonstrated in pig heart that cardiac mast cells, when exposed to C5a, rapidly degranulated and released histamine and thromboxane B 2 . In previous studies, 27 we have shown the presence of both C5a and thromboxane B 2 in postischemic cardiac lymph. This suggested to us that mast cell degranulation might be an important part of the ischemia/reperfusion process.…”
Section: Potential Role For Mast Cellsmentioning
confidence: 58%
See 1 more Smart Citation
“…26 Furthermore, Ito et al 15 demonstrated in pig heart that cardiac mast cells, when exposed to C5a, rapidly degranulated and released histamine and thromboxane B 2 . In previous studies, 27 we have shown the presence of both C5a and thromboxane B 2 in postischemic cardiac lymph. This suggested to us that mast cell degranulation might be an important part of the ischemia/reperfusion process.…”
Section: Potential Role For Mast Cellsmentioning
confidence: 58%
“…10,30 Although this model has been used extensively in our research, 2 important articles require review here to understand the significance of the present findings. First, in previous experiments, 27 we have demonstrated a prompt rise of thromboxane B 2 during early reperfusion, which may provide additional evidence for mast cell degranulation during the ischemia and reperfusion events. The second important point stems from one of our earliest studies, in which we measured the appearance of creatine kinase and phosphorylase b in the cardiac lymph.…”
Section: And 9)mentioning
confidence: 59%
“…If there is insufficient enzymatic protection, the presence of catalytically active metal ions will lead to the production of other, highly reactive, mem brane-destructive intermediates, such as hy droxyl radicals [23], Conflicting data have been reported on the possible connection between arachidonic-acid-derived eicosanoid production and reactive oxygen intermediates formed during ischemia-reperfusion. Since cycloox ygenase (and lipoxygenase) can be inhibited by several antioxidants and an increased production of molecular oxygen species may enhance oxygenase activity, an elevation in eicosanoid output and consequently the ef fectiveness of scavengers in limiting post ischemic eicosanoid production could be an ticipated [7,24], Such findings have actually been demonstrated in some experimental models [25,26]. Conversely, the generated oxygen radicals feed back to deactivate the cyclooxygenase, and antioxidant treatment could therefore lead to an enhanced eicosa noid synthesis [6,27], Severe free radical damage can result in major losses of mem brane phospholipids, reducing their avail ability for eicosanoid formation, and thus decreases in the production of 6-keto-PGFia and TxB2 could occur [28].…”
Section: Discussionmentioning
confidence: 99%
“…48 The present results are consistent with the induction of PMN chemotaxis into the ischemic myocardium by activation of the complement cascade. Activated PMNs produce chemotactic factors such as leukotriene B4, platelet-activating factor and IL-8 in ischemic myocardium 4,43,45 and our results in CVFtreated rats suggest that complement function rather than activation of PMNs is the factor involved in the accumulation of PMNs in the ischemic myocardium because the activation of PMNs, when complement was depleted, resulted in a significantly smaller accumulation of PMNs in the myocardium (group 2). With an intact complement system, in vivo myocardial ischemia -reperfusion injury may be exacerbated, accompanied by PMN infiltration, confirming that the management of complement contributes to a reduction of IS associated with myocardial PMN infiltration.…”
Section: Discussionmentioning
confidence: 53%
“…First, intravascular PMNs might cause myocardial injury, because the supernatant of activated PMNs induces injury to isolated cardiac myocytes in vitro. [37][38][39] The majority of PMNs are in the intravascular space during the first few hours after ischemia -reperfusion 40 and it is possible that the cyclooxygenase -lipoxygenase system, 41,42 reactive oxygen species, 43,44 inflammatory cytokines, 6,45 such as interleukin (IL)-8, tumor necrosis factor-and IL-6, in part derived from PMN activation, injure the myocardium at risk in an inflammatory cascade. In this context, the MPO activity in the ischemic area of groups 2 and 3 was significantly higher compared with each non-ischemic area, whereas it was less than that of group 1.…”
Section: Discussionmentioning
confidence: 99%